The Digital Marketing and Customer Management Assistance at Astajava Coffee and Roastery - Faturrohman, M. Deisry; Audita Nuvriasari (Asian Journal of Community Services, 2023)
The objective of the service program was implemented at Astajava Coffee and Roastery with the aim of increasing the effectiveness of digital marketing through training in creating marketing content with the Canva application and building a customer loyalty program. The implementation method involves surveying company needs, implementing training programs, evaluations, customer satisfaction surveys, creating a customer database, and creating a member loyalty program. The results include developing employee skills in creating engaging marketing content through Canva, innovation in the selection of promotional content, increasing the number of Instagram followers, and positive customer response to the loyalty program.